Comparison of Rape in Indonesian Positive Law, Islamic Law and South Korean Law - Sitompul, Mhd. Nasir; Iskandar Muda Sipayung; Aisyah; Rilawadi Sahputra; Dody Safnul (Faculty of Law, Universitas Pekalongan, 2024)
This paper initiated the study of Comparative Law in criminal rape. The crime of rape is a crime as a violation of human rights. Rape is a form of crime that causes loss and anxiety in the community, rape often occurs but is always difficult to prosecute because one of them is the reluctance of victims to report it, this is because there is still a culture of shame attached to the community. Each country has its own atauran in handling and tackling rape cases that occur in the country. In making a legal comparison, of course, what is interesting to compare is the comparison with other countries that adhere to the civil law legal system and other countries that adhere to the common law system. This study uses normative research methods with legislation and conceptual approach. There are similarities and differences in the criminal regulation of rape in positive law in Indonesia , Islamic law and statutory rape in South Korea. The similarities lie in: first, the arrangements regarding rape by force or threat of violence; Second, The Rape of minors. While the differences that can be compared are: 1) rape of disability; 2) the element of consent; 3) length of punishment; 4) the object of Rape; 5) Blood rape; and 6) rape in marriage (marital rape).